Late Pleistocene‐Holocene Slip Rate Along the Hasi Shan Restraining Bend of the Haiyuan Fault: Implication for Faulting Dynamics of a Complex Fault System. Issue 12 (4th December 2019) - Matrau, R.; Klinger, Y.; Van der Woerd, J.; Liu‐Zeng, J.; Li, Z.; Xu, X.; Zheng, R.
Abstract: The Haiyuan fault is a major left‐lateral strike‐slip fault at the boundary between northeast Tibet and the Gobi platform. Combining measurements of offset alluvial terraces with 10 Be‐ 26 Al cosmogenic radionuclides dating, we bracket the late Quaternary slip rate along the Hasi Shan fault section (37°00′N, 104°25′E) of the Haiyuan fault. At our reference site, terrace‐riser offsets for five successive terraces range from 5 to 200 m, and associated cosmogenic radionuclide ages range from 9 ± 3 to 44 ± 7 kyr. These measurements yield a geological slip rate between 2.7 and 3.0 mm/year. Extending the offset measurements to the entire Hasi Shan front, it yields a slip rate of 3.2 ± 0.2 mm/year over the last 50 kyr. Our rate is consistent with the lower estimates of other long‐term rates of 4 to 5 mm/year, as well as with geodetic rates of 3 to 5 mm/year, determined in the same area. About 150 km farther west, however, Holocene terraces and moraines offsets have suggested higher slip rate values, between 6 and 15 mm/year. We interpret such discrepancy between rates determined along the western section of the Haiyuan fault and rates determined in the Hasi Shan section as being related to the complex geometry of the Haiyuan fault system along its eastern part, with several active strands moving at the same time and resulting in distributed slip among several sections of the fault system. Key Points: Slip rate along the Hasi Shan section of the Haiyuan fault is determined from numerous offsets and cosmogenic exposure dates over a period of 50, 000 years The Hasi Shan fault strand horizontal slip rate is about 3.2 mm/year; this rate is stable over 50, 000 years; the uplift rate is about 0.5 mm/year Combining slip rate for the Hasi Shan strand and all subparallel stands yields a slip rate of 5 to 7 mm/year for the Haiyuan fault system